Median preoptic nucleus excitatory neurotransmitters in the maintenance of hypertensive state - Mourao, Aline A.; Soares de Mello, Aryanne B.; Dos Santos Moreira, Marina C.; Rodrigues, Karla L.; Lopes, Paulo R.; Xavier, Carlos H.; Gomes, Rodrigo M.; Freiria-Oliveira, Andre H.; Blanch, Graziela T.; Colombari, Eduardo [UNESP]; Pedrino, Gustavo R. (Elsevier B.V., 2018)
The crucial role of the median preoptic nucleus (MnPO) in the maintenance of hydroelectrolytic balance and autonomic regulation have been highlighted. Recently, the participation of the MnPO in the control of sympathetic nerve activity was demonstrated in essential hypertension model. However, peculiarities on the neurochemical changes underlying the differential role of MnPO during hypertension remain to be clarified. Therefore, this study aimed to investigate the main excitatory pathways that modulate MnPO neurons in hypertensive rats. Spontaneously hypertensive rats (SHR) and rats submitted previously to the Goldblatt protocol (two kidneys; one clip; 2K1C) were used. Rats of both groups (250 to 350 g, n = 6) were anesthetized with urethane (1.2 g/kg,i.v.) and instrumented to record mean arterial pressure (MAP), heart rate (HR) and renal sympathetic nerve activity (RSNA). Nanoinjection (100 nl) of saline (NaCl, 150 mM), losartan (AT1 receptor antagonist; 10 mM) and kynurenic acid (glutamate receptor antagonist; 50 mM) into the MnPO were performed. In 2K1C rats, glutamatergic blockade promoted decreases in MAP and RSNA (-19.1 +/- 0.9 mmHg, -21.6 +/- 2.8%, p < 0.05) when compared to saline (-0.4 +/- 0.6 mmHg, 0.2 +/- 0.7%, p < 0.05). Angiotensinergic inhibition also reduced these parameters (-11.5 +/- 1.2 mmHg, -10.5 +/- 1.0%, p < 0.05) in 2K1C. In SHR, Kynurenic acid nanoinjections produced hypotension and sympathoinhibition (-21.0 +/- 2.5 mmHg, -24.7 +/- 2.4%, p < 0.05), as well losartan nanoinjections (-9.7 +/- 1.2 mmHg; p < 0.05) and RSNA (-12.0 +/- 2.4%, p < 0.05). These findings support the conclusion that a tonic excitatory neurotransmission exerted by angiotensin II, and mostly by glutamate in the MnPO could participate in the modulation of blood pressure and RSNA independent on whether hypertension is primarily neurogenic or is secondary to stenosis in renal artery.
Keywords: MnPO; 2K1C; SHR; Glutamate; Angiotensin II